Increasing Prevalence and Stable Incidence Rates of Inflammatory Bowel Disease Among First Nations: Population-Based Evidence From a Western Canadian Province. Issue 4 (25th May 2021) - Peña-Sánchez, Juan Nicolás; Osei, Jessica Amankwah; Marques Santos, Jose Diego; Jennings, Derek; Andkhoie, Mustafa; Brass, Colten; Bukassa-Kazadi, Germain; Lu, Xinya; Johnson-Jennings, Michelle; Porter, Linda; Porter, Rob; Quintin, Carol-Lynne; et al.
Abstract: Background: There is limited to no evidence of the prevalence and incidence rates of inflammatory bowel disease (IBD) among Indigenous peoples. In partnership with Indigenous patients and family advocates, we aimed to estimate the prevalence, incidence, and trends over time of IBD among First Nations (FNs) since 1999 in the Western Canadian province of Saskatchewan. Methods: We conducted a retrospective population-based study linking provincial administrative health data from the 1999-2000 to 2016-2017 fiscal years. An IBD case definition requiring multiple health care contacts was used. The prevalence and incidence data were modeled using generalized linear models and a negative binomial distribution. Models considered the effect of age groups, sex, diagnosis type (ulcerative colitis [UC], Crohn disease [CD]), and fiscal years to estimate prevalence and incidence rates and trends over time. Results: The prevalence of IBD among FNs increased from 64/100, 000 (95% confidence interval [CI], 62-66) in 1999-2000 to 142/100, 000 (95% CI, 140-144) people in 2016-2017, with an annual average increase of 4.2% (95% CI, 3.2%-5.2%). Similarly, the prevalence of UC and CD, respectively, increased by 3.4% (95% CI, 2.3%-4.6%) and 4.1% (95% CI, 3.3%-4.9%) per year. In contrast, the incidence rates of IBD, UC, and CD among FNs depicted stable trends over time; no statistically significant changes were observed in the annual change trend tests. The ratio of UC to CD was 1.71. Conclusions: We provided population-based evidence of the increasing prevalence and stable incidence rates of IBD among FNs. Further studies are needed in other regions to continue understanding the patterns of IBD among Indigenous peoples.